The effects of taxes and benefits on income distribution in the enlarged EU - EUROMOD; Paulus, Alari; Cok, Mitja; Figari, Francesco; Hegedüs, Peter; Kump, Natasa; Lelkes, Orsolya; Levy, Horacio; Lietz, Christine; Lüpsik, Silja; Mantovani, Daniela; Morawski, Leszek; et al. (Colchester, 2009)
"Tax and benefit systems in the enlarged EU vary significantly in size and structure. We examine how taxes and benefits shape income distributions in 19 EU countries, focusing on the differences between Western European countries (EU15) and Eastern European countries (Estonia, Hungary, Poland, Slovenia). We use EUROMOD, the European tax-benefit microsimulation model, which simulates taxes and benefits for representative samples of household micro-data and through a common framework which allows the analysis of cross-country differences on a comparable basis. The analysis concentrates on the distribution and composition of incomes, and the effect of taxes and benefits on poverty and inequality"